Principles of developing a well-rounded program of physical rehabilitation for female students in the special medical group with consideration of physical activity impairment - N. R. Golod (H.S. Skovoroda Kharkov National Pedagogical University, 2015)
Purpose : to highlight the main provisions of a comprehensive physical rehabilitation program for students of special medical group based on violations of the motor capacity. Material : testing 24 students of special medical group and the same number of their healthy peers on standardized tests of physical qualities. To reflect the movement disorders applied functional movement screen. Results : a program of rehabilitation of the students included: lifestyle modification; morning hygienic gymnastics; kinesitherapy (using yoga fitness, functional training); aerobic exercise (swimming, Nordic Walking, jogging, aerobics wellness); massage. First presented a unified approach to working with students of special medical groups - selection based on load capacity motor disorders according to the results of tests of functional movement screen. The complexity of the impact of the program involves the impact on the physical, social and mental health components. Conclusions : the author's program of physical rehabilitation of students of special medical group is complex.